River Park Assessment: 2D Hydraulic Watercourse Modeling for Nature-based Solutions in Urban Area - Halecki, Wiktor; Bedla, Dawid; Plesiński, Karol; Ziernicka-Wojtaszek, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Over time, fragmentation of semi-natural habitats in urban areas has become a pressing concern, disrupting ecological processes within cities. The focus on preserving open ecosystems has grown, highlighting the need to enhance resilience in urban riverside areas for effective ecosystem restoration. Comprehensive studies on river valleys, considering both hydrology and ecology, play a crucial role in urban river ecosystem development.
Keywords: 2D modeling; hydraulic properties; urban climate resilience; linear buffer park